PEMANFAATAN BIJI PEPAYA DALAM PEMBUATAN BUBUK KOPI KOMBINASI DENGAN BIJI KOPI ARABIKA ASAL SUMBA BARAT - Bani, Dubu Bani; Mushollaeni, Wahyu; Sasongko, Pramono (Universitas Tribhuwana Tunggadewi, 2023)
The research aimed to determine chemical and physical content of coffee powder combined with papaya seeds and Arabica coffee beans from West Sumba. This research method is an experiment using a Completely Randomized Design (CRD) with one factor. The treatment factors were papaya seed powder and Arabica coffee powder there are four treatments, and repeated 3 times, so there were 12 experimental units. The best research results were B4 treatment with a combination of 25% papaya seeds and 75% Arabica coffee beans with a caffeine content of 0.93%, water content of 1.17%, ash content of 2.82%, color preference of 4.33 categories, preference aroma 4.24 like categories, and taste preferences 4.12 like categories. The highest yield value (NH) shows the best treatment is B4 treatment with a total NH value of 0.60. Analysis of business feasibility in the best treatment with an RCR of 1.28. R/C Ratio 1 with selling price Rp. 11,500/Packaging 150g.